Exploring Fetal Sex Dimorphism in the Risk Factors of Gestational Diabetes Mellitus—A Prospective Cohort Study - Wang, Wen-Juan; Zhang, Lin; Zhang, Dan-Li; Zheng, Tao; He, Hua; Fang, Fang; Zhang, Jun; Ouyang, Fengxiu; Luo, Zhong-Cheng; , Shanghai Birth Cohort Study (Frontiers in Endocrinology, 2019)
Gestational diabetes mellitus (GDM) is a common pregnancy complication. Its etiology remains incompletely understood. Studies in recent years suggest that fetal sex may affect maternal metabolic milieu during pregnancy. We sought to assess whether there is fetal sex dimorphism in the risk factors of GDM. In a prospective pregnancy cohort in Shanghai, China, we studied 2435 singleton pregnant women without pre-existing diabetes. GDM was diagnosed according to the International Association of Diabetes and Pregnancy Study Groups (IADPSG)’ criteria. Log-binomial models were applied to obtain the adjusted relative risk (aRR). A total of 380 (15.6%) women developed GDM. Family history of diabetes was associated with an increased risk of GDM in women bearing a female fetus [aRR 1.74 (1.27-2.40), p<0.001], but not in women bearing a male fetus (p=0.68) (test for interaction, p=0.03). Alcohol drinking was associated with an increased risk of GDM in women bearing a male fetus only (p=0.023), although the test for interaction did not reach statistical significance (p=0.055). In conclusion, family history of diabetes was associated with an increased risk of GDM in women bearing a female fetus only in this Chinese pregnancy cohort. There may be a need to consider fetal sex dimorphism in evaluating the risk factors of GDM.